ANALISIS PERTUMBUHAN EKONOMI DAN TENAGA KERJA TERHADAP PENURUNAN JUMLAH PENDUDUK MISKIN DI INDONESIA - FONI NURLITA, MHD. ARIF (Lembaga Penelitian dan Pengabdian Masyarakat IAI An-Nadwah Kuala Tungkal, 2021)
This study aims to analyze economic and labor growth on the decline in thenumber of poor people in Indonesia based on 2010-2020 data. The method usedin this study is quantitative, which means using data in the form of numbers andanalysis using multiple linear regression statistics. In this study, the type of dataused is secondary data taken from BPS (Central Statistical Agency) data which isthen used as material in analyzing the influence of variables on economic growth,labor, and the poor. SPSS variant 26 factual application is used in handlinginformation. Based on the research that has been done, the results obtained thatthe variable economic growth has no positive and insignificant effect on the poor,while the labor variable has a significant effect on the poor in Indonesia and thevariables of